2021
DOI: 10.1080/19475411.2021.1972053
|View full text |Cite
|
Sign up to set email alerts
|

Ionic conductive gels based on deep eutectic solvents

Abstract: Ionic conductive gels are promising soft conductors for stretchable and flexible electronics. Unfortunately, the basic requirements for an ideal ionic conductive gel, including environmental and chemical stability as well as low toxicity and low cost do not usually coincide in one material. Here we report an ionic conductive gel containing deep eutectic solvents (DES), which are specialized ionic liquids composed of propylene glycol (PG, hydrogen bonding donor) and various salts. In experiments, the DES-gel lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…As expected, BioeGel0% presented a predictable conductivity of 72 mS m –1 according to Manning’s theory, considering that the eutectic mixture and collagen dielectric constants are the main ones responsible for ionic conductivity. Furthermore, it was found that similar ionic gels exhibited conductivities in the same order of magnitude as that of BioeGels . Interestingly, the k values of BioeGels loaded with TA@CNC yielded conductivities higher than that of BioeGel0%.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…As expected, BioeGel0% presented a predictable conductivity of 72 mS m –1 according to Manning’s theory, considering that the eutectic mixture and collagen dielectric constants are the main ones responsible for ionic conductivity. Furthermore, it was found that similar ionic gels exhibited conductivities in the same order of magnitude as that of BioeGels . Interestingly, the k values of BioeGels loaded with TA@CNC yielded conductivities higher than that of BioeGel0%.…”
Section: Resultsmentioning
confidence: 89%
“…Furthermore, it was found that similar ionic gels exhibited conductivities in the same order of magnitude as that of BioeGels. 57 Interestingly, the k values of BioeGels loaded with TA@CNC yielded conductivities higher than that of BioeGel0%. In this sense, previous studies suggested that the addition of CNC as well as a crosslinker such as TA can enhance the ionic conductivity.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…The above reports have demonstrated the anti-freeze properties of conventional hydrogels. Although there are certain research results and experimental methods have been promoted [66] Copyright 2021, The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.…”
Section: Other Strategies To Prepare Antifreezing Hydrogelsmentioning
confidence: 99%
“…Figure 5. a) Construction strategy of DESs-gel; b) DESs-gel phosphor digital display device. Adapted with permission [66]. Copyright 2021, The Author(s).…”
mentioning
confidence: 99%
“…Therefore, DES based ionic gels had been greatly favored. Liu et al 18 prepared ionic gels with good environmental stability (anti‐drying) and chemical stability (anti‐corrosion) by using DES (composed of propylene glycol and various chloride salts) as solvent. However, the maximum tensile strength and the tensile strain was only 12.23 kPa and 127%, respectively.…”
Section: Introductionmentioning
confidence: 99%